(untitled) (Economics and region, 2018)
The article presents an overview of the technologies of personnel management and administration in the context of the organization development. The improvement of personnel management technology in organizations was given. The basis of modern development laid new concepts that help to influence the work of the entire team, which ultimately contributes to the effective functioning of the enterprise. The necessity of development of staff administration for the purpose of effective management was substantiated. There were determined that personnel management refers to the functions that many employers now refer to as Human Resources. These are the functions that the human resources staff performs relative to the organization’s employees. These functions include recruiting, hiring, compensation and benefits, new employee orientation, training, and performance appraisal systems.